Evaluating the level of knowledge and attitude towards evidence- based medicine among pharmacists: perceived educational need in the pharmacy curriculum - Sina Valinejad; Farzaneh Karamitanha; Nima Motamed; Mehran Mohseni (Zanjan University of Medical Sciences and Health Services, 2022)
Background & Objective: Evidence-based medicine (EBM) integrates the best available evidence from authentic studies with clinical expertise and patients' values, helping pharmacists to have access to the best available evidence to respond to clinical questions. The present study aimed to assess the level of awareness and attitude of pharmacists as the initial step to improve these practices. Materials & Methods: The instrument used in this cross-sectional study was a questionnaire of awareness and attitudes towards EBM and its related terms (Abofarha et al., 2014). After localization, the questionnaire was provided to the pharmacists working in the pharmacies of Zanjan province and pharmacy students in the last two years of university, and the results were assessed. Results: The participation rate was 75%, and 66.8% of subjects were familiar with the concept of EBM. The participants who did not have sufficient knowledge had higher mean age scores in comparison with those who did not (P=0.001). Moreover, 74.1% of students and 60% of graduates in this study showed sufficient knowledge and the difference between the two groups was significant (P= 0.023). In addition, 84.1% of the participants had a positive attitude towards EBM. Students and graduates did not significantly differ in terms of attitude. Conclusion: As evidenced by the results of this study, pharmacists and pharmacy students in Zanjan province had a good knowledge of EBM terms. Moreover, it was found that participants with more work experience were less knowledgeable in this regard. The majority of them had positive attitudes towards EBM, and it is suggested to include EBM in the pharmacy curriculum to increase students' knowledge in this regard.